Enhancing the productivity of the bi-enzymatic convergent cascade for ɛ-caprolactone synthesis through design of experiments and a biphasic system. Issue 46 (17th November 2016) - Bornadel, Amin; Hatti-Kaul, Rajni; Hollmann, Frank; Kara, Selin
Abstract: A two-step Design of Experiments (DoE) strategy followed by a two-liquid-phase system (2LPS) was applied to enhance the ɛ-caprolactone yield in the cyclohexanone monooxygenase (CHMO)-alcohol dehydrogenase (ADH) convergent cascade system. The key reaction parameters were identified and optimized for the determination of an optimal operational window for the aqueous media. In the 2LPS system, high partitioning of the lactone product was observed in 2-MeTHF and in toluene; however, these solvents led to drastically reduced enzymatic activity. Dodecane was chosen as the non-miscible organic phase owing to the enzymes' high residual activity, despite the low partitioning of the lactone. Cyclohexanone concentrations up to 75 mM were applied in the aqueous media. The turnover numbers for the nicotinamide cofactor and for the ADH reached up to 980 and 392, 000, respectively whereas a turnover number value of 5600 was achieved for the CHMO. By employing a 2LPS, whereby 91 mM of cyclohexanone was applied in the second phase, turnover numbers were slightly increased. Graphical abstract: